Inflation targeting in low-income countries: Does IT work? - Michael F. Bleaney; Atsuyoshi Morozumi; Zakari Mumuni (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2020)
Previous research on inflation targeting (IT) has focused on high-income countries (HICs) and emerging market economies (EMEs). Only recently has enough data accumulated for the performance of IT in low-income countries (LICs) to be assessed. We show that IT has not so far been as effective in reducing inflation in LICs as in EMEs. Relatively weak institutions, a typical feature of LICs, help explain this result. Our interpretation is that poor institutions, leaving fiscal policy unconstrained, impair central banks' ability to conduct monetary policy in a way consistent with IT.
Keywords: E52; E58; O23; 330; Inflation targeting; Low-income countries; Institutions